2012
DOI: 10.5114/pg.2012.30505
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of insulin, insulin-like growth factor I, vascular endothelial growth factor and gastrin in patients with colon adenomas and colorectal cancer

Abstract: Słowa kluczowe: rak jelita grubego, insulina, insulinopodobny czynnik wzrostu I, gastryna, śródbłonkowy czynnik wzrostu naczyń. Key words: colon cancer, insulin, insulin-like growth factor I, gastrin, vascular endothelial growth factor.Adres do korespondencji: dr n. med. Aleksandra Kaczka, Klinika Chorób Przewodu Pokarmowego, Uniwersytet Medyczny, ul. Kopcińskiego 22, Polska, tel.: +48 42 678 64 80, Artykuł oryginalny/Original paper StreszczenieWstęp: Kancerogeneza jelita grubego jest procesem wieloetapowym, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Most previous studies have failed to find an association between colorectal adenoma and C-peptide (27, 28). In contrast, several studies have observed a positive association between C-peptide and colorectal cancer (23-25).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Most previous studies have failed to find an association between colorectal adenoma and C-peptide (27, 28). In contrast, several studies have observed a positive association between C-peptide and colorectal cancer (23-25).…”
Section: Discussionmentioning
confidence: 97%
“…The data for leptin are inconsistent, with some studies finding a positive association for colorectal adenoma (15) and cancer (16-18) and others an inverse association for colorectal adenoma (8) and cancer (8, 19-21). C-peptide is an inactive by-product and marker of insulin production (22) and has been positively associated with colorectal cancer (23-25); in contrast, the evidence for a positive association with colorectal adenoma is limited to one (26) of the three (27, 28) studies conducted. Circulating homocysteine has been positively associated with hyperinsulinemia (29), and this highly reactive metabolite can promote inflammation, tissue damage, cardiovascular disease, and carcinogenesis (30, 31).…”
Section: Introductionmentioning
confidence: 99%
“…The pathological explanation for this connection has led to a so-called hyperinsulinemia hypothesis [11]; increased insulin level could promote colorectal tumor growth and act as a cell mitogen [12]. In support of this hypothesis, positive association between serum C-peptide concentration and an increased colorectal cancer risk were found in several studies [13][15]. Although studies have reported a clear association of DM and hyperinsulinemia with the risk of colorectal cancer [16], association between DM and the risk of mortality in colorectal cancer patients is somewhat unclear.…”
Section: Introductionmentioning
confidence: 98%
“…[11] The varying incidences of colon polyps according to insulin concentration have been examined in numerous studies; however, the results are inconsistent. [14][15][16][17][18] In particular, most previous studies have focused on adenomas, [9,14,15,23,24] so study data on the effects of insulin on nonadenomatous polyps, such as hyperplastic polyps, are lacking.…”
Section: Discussionmentioning
confidence: 99%